Non-surgical treatment for periodontitis and peri-implantitis: longitudinal clinical and bacteriological findings—A case report with a 7-year follow-up evaluation. (July 2021) - Shiba, Takahiko; Watanabe, Takayasu; Komatsu, Keiji; Koyanagi, Tatsuro; Nemoto, Takashi; Ohsugi, Yujin; Michi, Yasuyuki; Katagiri, Sayaka; Takeuchi, Yasuo; Ishihara, Kazuyuki; Iwata, Takanori
The aim of this report is to show that periodontitis and peri-implantitis with horizontal bone resorption in a 68-year-old male patient were successfully treated by non-surgical treatment. Scaling with an ultrasonic device was performed for moderate periodontitis around the mandibular left first premolar and moderate peri-implantitis around the maxillary right molar implants. Root planing with a metal curette was performed for the periodontal site, and debridement with a plastic curette was performed for the peri-implant site. A month after treatment, probing depth decreased from 5 to 2 mm at the periodontal site and 8 to 3 mm at the peri-implant site. The investigation of bacterial composition by sequencing the 16S rRNA gene amplicons showed that the composition similarly changed at both sites, 5 years after treatment; the change reflected the typical recovery of periodontitis. The clinical condition was maintained for 7 years after treatment at both sites. This was a successful case of non-surgical treatment for peri-implantitis with horizontal bone resorption, promoting recovery of the microbiota from dysbiotic shift.